Predictors of lower extremity amputation in patients with diabetic foot ulcer - Umashankar, Girish Thimmanalli; M. S., Anil Kumar; Shahid, Mohammed (International Surgery Journal, 2019)
Background: Diabetic foot lesions are responsible for more hospitalisations than any other complication of diabetes and diabetes is a predominant aetiology for non-traumatic lower extremity amputations. Authors, therefore, examined the clinical characteristics that best predict poor outcome in a large population of diabetic foot ulcer patients. The objective of the study was to describe independent predictors for lower extremity amputation in patients with a diabetic foot ulcer and to validate the predictive value of PEDIS (IWGDF) classification system for a diabetic foot ulcer. Methods: A retrospective study of 197 patients presenting with diabetic foot ulcer presenting to a tertiary care hospital in Mysuru, India. The recorded parameters were age, sex, various risk factors, laboratory parameters, the presence of DM-related complications and ulcer characteristics as determined by PEDIS system. The main outcomes recorded were healed ulcer and amputation. Results: Authors have found that factors strongly associated with risk of amputation are (in order of strength): PVD, past amputation, nephropathy, past ulcer, ulcer duration, TLC, Hb and sr. creatinine. Authors also validated the PEDIS scoring system as an effective classification system with prognostic value. The PEDIS score of >7 is a highly significant predictor of adverse outcome (amputation) of diabetic foot ulcer. Conclusions: Several risk factors for lower extremity amputation in a patient with diabetic foot ulcer were identified. An integrated risk-assessment model including the above significant risk factors and PEDIS system can be developed that is both clinically accurate as well as quick to assess for predicting the adverse outcome in a patient of diabetic foot ulcer and providing an opportunity to save the limb.